2015
DOI: 10.1083/jcb.201412010
|View full text |Cite
|
Sign up to set email alerts
|

KLP-7 acts through the Ndc80 complex to limit pole number in C. elegans oocyte meiotic spindle assembly

Abstract: KLP-7/MCAK regulates kinetochore–microtubule attachment and spindle tension to promote the coalescence of early spindle pole foci, which produces a bipolar structure during the acentrosomal process of oocyte meiotic spindle assembly in C. elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 74 publications
7
59
1
1
Order By: Relevance
“…2C). In agreement with a previous study and with our in utero analysis, we found that spindles assembled in KLP-7-depleted oocytes were multipolar (Connolly et al, 2015) ( Fig. 2D).…”
Section: In Utero Imaging Reveals That Klp-7 Is Required For the Initsupporting
confidence: 82%
See 4 more Smart Citations
“…2C). In agreement with a previous study and with our in utero analysis, we found that spindles assembled in KLP-7-depleted oocytes were multipolar (Connolly et al, 2015) ( Fig. 2D).…”
Section: In Utero Imaging Reveals That Klp-7 Is Required For the Initsupporting
confidence: 82%
“…In the C. elegans oocyte, KLP-7 has been proposed to limit metaphase spindle pole numbers by correcting improper kinetochore-microtubule attachments, but its precise function throughout the two meiotic divisions remains elusive (Connolly et al, 2015;Han et al, 2015). Here, we show the crucial meiotic function of KLP-7 in preventing ectopic microtubule assembly that otherwise leads to spindle disorganization and chromosome segregation defects.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations